The Use of Social Media for the Promotion of Catering Services during the First Wave of the Coronavirus Pandemic. Theoretical and Analytical Considerations on the Example of Facebook - Marta SIDORKIEWICZ (Communications of International Proceedings, 2020)
The theoretical aim of this article is to organize the hypothetical aspects of catering services and promotion, with particular emphasis on promotion on the Internet, and in the empirical area, presenting the scope of e-promotional activities of the catering industry during the first wave of the coronavirus pandemic on the example of the social media Facebook. The article consists of three substantive parts, as well as introduction and summary. The first and second parts of the article mainly cover theoretical considerations regarding the essence of catering services and the basic aspects of promotion in the traditional and modern approach, with particular emphasis being put on social media. The third part of the study discusses the results of qualitative research conducted using the method of observation on the type of undertaken activity of the catering industry in the field of e-promotion based on social media, namely Facebook. The time scope of the qualitative research was the lockdown period in Poland (March - May 2020), whereas the subjective scope encompassed establishments providing catering services in Poland.
Keywords: Catering Services; Promotion; Social Media; Coronavirus